Effects of Ethanolic Extract of Curcuma Longa on Cardiac Biomarkers of Doxorubicin-Induced Rats - Lydia Ernawati Rahayu; Linda Chiuman; Chrismis Novalinda Ginting; Sahna Ferdinand Ginting (Majalah Kedokteran Bandung, 2020)
Cardiotoxicity is a condition where damages caused by toxic chemical exposure are observed in heart and blood vessels. Doxorubicin is the most common chemotherapy agents for various types of cancer therapy. However, doxorubicin is converted into doxorubicinol known to trigger cardiac disfunctions and release of several cardiac biomarkers, such as CK-MB and LDH. Turmeric is known to be an alternative medical treatment that has the effect of neutralizing oxidative stress. This study aimed to evaluate CK-MB and LDH levels in doxorubicin-induced rats (20 mg/kgBW) that received turmeric ethanolic extract from curcuma. This was an experimental study conducted in February 2020 in the Faculty of Pharmacy Universitas Sumatera Utara. The rats were divided into six group and each group consisted of wistar albino male rats. The groups were normal (CMC-Na), positive control (Vitamin E 1%+Dox 20 mg/kgBW), negative control (Dox 20 mg/kgBW), treatment I (EEC 100 mg/kgBW+Dox 20 mg/kgBW), treatment II (EEC 300 mg/kgBW+Dox 20 mg/kgBW), and treatment III (EEC 500 mg/kgBW+Dox 15 mg/kgBW). Doxorubicin was given 5 mg/kgBW once a week for four weeks. Results showed that the groups that received 100 mg/kg BW, 300 mg/kgBW, and 500 mg/kgBW of turmeric ethanol extract demonstrated a reducing effect on the biomarkers of cardiac damage, i.e. CK-MB and LDH. Statistically, serum CK-MB and LDH levels at dose 500 mg/kgBW showed no significant differences (p>0.05) with the normal and positive treatment group. In conclusion, turmeric has a cardioprotective effect. Pengaruh Kardioprotektif Ekstrak Etanol Curcuma Longa pada Tikus yang Diinduksi DoxorubicinKardiotoksisitas adalah kondisi terjadinya jantung dan pembuluh darah akibat paparan kimia. Doxorubicin diubah menjadi doxorubicinol yang diketahui menyebabkan gangguan fungsi jantung dan pelepasan biomarker jantung sseperti CK-MB dan LDH. Kunyit dikenal sebagai pengobatan alternatif yang memiliki efek menetralkan stres oksidatif. Penelitian ini dilakukan pada Februari 2020 di Fakultas Farmasi Universitas Sumatera Utara. Tujuan penelitian ini adalah mengevaluasi kadar CK-MB dan LDH pada tikus yang diberi ekstrak etanol kunyit yang diinduksi doksorubisin (20 mg/kgbb). Penelitian dibagi menjadi enam kelompok dan tiap-tiap kelompok terdiri atas 4 ekor tikus wistar albino jantan: normal (CMC-Na), kontrol positif (Vitamin E 1%+Dox 20 mg/kgBB), kontrol negatif (Dox 20 mg/kgBB), group I (EEC 100 mg/kgBB+Dox 20 mg/kgBB), group II (EEC 300 mg/kgBB+Dox 20 mg/kgBB), dan group III (EEC 500 mg/kgBB+Dox 15 mg/kgBB). Doxorubicin 5 mg/kgBB diberikan 4 kali. Hasil penelitian menunjukkan bahwa kelompok yang diberi ekstrak etanol kunyit dengan dosis 100 mg/kgBB, 300 mg/kgbb, 500 mg/kgBB memiliki efek penurunan biomarker kerusakan jantung yaitu CK-MB dan LDH. Berdasar atas hasil uji statistik kadar CK-MB dan LDH serum pada dosis 500 mg/kgBB tidak terdapat perbedaan yang bermakna (p>0,05) dengan kelompok normal dan positif, dapat disimpulkan bahwa kunyit memiliki efek kardioprotektif.